2012
DOI: 10.1371/journal.pone.0040285
|View full text |Cite
|
Sign up to set email alerts
|

Common Protein Biomarkers Assessed by Reverse Phase Protein Arrays Show Considerable Intratumoral Heterogeneity in Breast Cancer Tissues

Abstract: Proteins are used as prognostic and predictive biomarkers in breast cancer. However, the variability of protein expression within the same tumor is not well studied. The aim of this study was to assess intratumoral heterogeneity in protein expression levels by reverse-phase-protein-arrays (RPPA) (i) within primary breast cancers and (ii) between axillary lymph node metastases from the same patient. Protein was extracted from 106 paraffin-embedded samples from 15 large (≥3 cm) primary invasive breast cancers, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Heterogeneous expression patterns have been described for EGFR in glioblastoma (20,21) and for HER2 in breast cancer (22,23), gastric cancer (24), and salivary duct carcinoma (20). In addition, biomarker studies in primary breast cancer have revealed a highly heterogeneous expression pattern for the whole HER family (25). Consequently, biomarker assessment and subsequent selection of an optimal targeted therapy remains challenging even when multiple biopsies are available.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous expression patterns have been described for EGFR in glioblastoma (20,21) and for HER2 in breast cancer (22,23), gastric cancer (24), and salivary duct carcinoma (20). In addition, biomarker studies in primary breast cancer have revealed a highly heterogeneous expression pattern for the whole HER family (25). Consequently, biomarker assessment and subsequent selection of an optimal targeted therapy remains challenging even when multiple biopsies are available.…”
Section: Introductionmentioning
confidence: 99%
“…The overall goal of the first research project [5] was to investigate the intratumoral heterogeneity of proteins with clinical relevance to breast cancer by analyzing 35 target proteins including 15 phosphorylated proteins. This included predictive markers for therapies targeting HER2 [50], diagnostic marker E-Cadherin [51], and prognostic markers including HER2, estrogen and progesterone receptors [42], and uPA and PAI-1 [52, 53].…”
Section: Resultsmentioning
confidence: 99%
“…All 35 proteins studied by reverse phase protein microarrays (RPPA) showed similar heterogeneity with a mean coefficient of variation (CV) of 31% (range 22–43%) within primary breast cancers and 35% (range 10–79%) within different lymph node metastases from the same patient [5]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these tests, one may not always know what fraction of the tissue expresses receptors to be targeted, the distribution pattern of receptors in tissue, and what is the expression at cellular level (density of receptors on cell surface), as these, in turn, vary depending on how the sample for biopsy has been taken [42]. This can also be ascribed to the heterogeneity of receptor expression at cellular level that a diseased tissue possesses [42]. For example, for tumors, cells at the periphery and those at the core of the tumor experience different microenviroments and blood supply, which leads to differences in expression at cellular level.…”
Section: Expression Characteristics Of Receptorsmentioning
confidence: 99%